PENYIDIKAN TINDAK PIDANA PELECEHAN SEKSUAL YANG DILAKUKAN OLEH ANAK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DI KEPOLISIAN RESOR KUANTAN SINGINGI - P, Purnama Sari; Firdaus, Emilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Children should be protected, especially children who are dealing with the law, has many laws that regulate and provide protection to children, it's just that the implementation of the criminal justice system in the field is still often encountered by children who commit crimes are not accompanied by legal protection, Their rights are taken away. Based on data at the Kuansing Police Resort criminal acts of sexual harassment committed by children in the process of investigation is not in accordance with the rules set out in Law Number 11 Year 2012 on the Criminal Justice System of Children. In this case the investigation of criminal acts of sexual harassment committed by the Kuansing Police Resort has not been maximized. The purpose of writing this thesis, namely; Firstly, to know the Criminal Sexual Abuse Investigation conducted by the Child at the Kuansing Police Resort, Secondly, To know the obstacles faced by the Criminal Investigation of Child Sexual Abuse, Third, To know the efforts made to overcome the barrier of Sexual Harassment Investigation What Children Do By Children.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at Kuantan Singingi Resort Police, while the population and sample were all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collecting technique in this research with interview and Literature study.From the results of research problems there are three main things that can be concluded. First, the investigation of sexual harassment conducted by the child does not work properly. Secondly, the obstacles faced by the PPA Unit are in the investigation of sexual harassment perpetrated by the child is the PPA Unit lack of personnel, the absence of RPK, the special detention room of the child in Polres Kuansing, PPA unit personnel lack experience in handling child cases, the perpetrator is difficult to give. Thirdly, the efforts made by PPA Unit in overcoming the obstacles of investigation of sexual harassment crime committed by the children are good cooperation among PPA Unit personnel, examined in the PPA Unit Working Unit and applying for funding budget in order to build the prisoner for children, and to increase the knowledge and quality PPA Unit investigators and coordinate with related agencies. The author's suggestion, Firstly, the examining is only the child investigator who has been authorized, Secondly, the child is sent home with the terms of the agreement, Third, increasing the investigator in the PPA Unit, increasing the knowledge and quality of the PPA investigator, in handling the case of sexual harassment committed By the child.Keywords: Investigation - Criminal act of sexual harassment – Committed By Child